Secure data transmission on a distributed cloud server with the help of HMCA and data encryption using optimized CP-ABE-ECC - Vengala, Dilip Venkata Kumar; Kavitha, D.; Kumar, A. P. Siva (Cluster computing, 2020)
The cloud computing (CC) model is diverse as well as has broad phenomena because of which it is being preferred widely. Due to security challenges, the user cannot utilize CC to its full potentials. Storing their sensitive data in an insecure place is not even an option for these users. Many techniques were posited for securely amassing the data in the cloud; however, during massive transmission, none of them maintain end-to-end security. And, prevailing methods are also unable to solve the key intricacy and avoid key secrecy exposé. Thus, for trouncing these disadvantages and also assuring the data transmission (DT) as of the source–destination, a secure DT scheme with the help of a distributed cloud server (CS) and data deduplication is proposed. The uploaded user data can well be amassed in disparate CS to ameliorate the user data’s security. It can be done by, first, extracting the features of the user data along with the CS. After that, the Hybrid Meerkat clan algorithm (HMCA) chose the CS, which is optimally centered on the features. Next, the SHA512 algorithm performs the data deduplication of the input user data. Subsequent to data deduplication, the input file is compressed and encrypted using a two-stage lempel–ziv algorithm and optimized CP-ABE-ECC algorithm. Lastly, the encrypted file is stored in the chosen CS. The experimentation is implemented to analyze the proposed method’s performance. The outcomes exhibited that the proposed work performed better contrasted to other prevailing algorithms.